2012
DOI: 10.5539/jedp.v2n1p151
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Bias in Teacher Ratings of Adolescents with ADHD

Abstract: Best practice assessment of childhood ADHD includes behavior ratings from multiple sources across multiple environments. However, adolescents in secondary schools interact with several teachers each day, and research has shown that teacher perceptions of the same child can be highly inconsistent. As a result, rating scale data can be equivocal, depending on which teachers are selected. The intent of the present study was two-fold: 1) to assess the consistency between teacher behavior ratings of adolescents wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The results of the Colomer et al (2020) study indicate that adolescent appraisals of their achievement are typically as accurate as parent reports and more accurate than teacher reports. This may be because secondary school teachers typically teach more than 100 students per semester, and the inter-rater reliability is low (Schultz & Evans, 2012). A key implication of the current study is that adolescents should also be asked to complete the self-report versions of behavior rating scales, and unless parents or teachers report clinical levels of oppositional behaviors, the adolescent ratings should generally be considered as valid.…”
Section: Psychological Assessmentmentioning
confidence: 97%
“…The results of the Colomer et al (2020) study indicate that adolescent appraisals of their achievement are typically as accurate as parent reports and more accurate than teacher reports. This may be because secondary school teachers typically teach more than 100 students per semester, and the inter-rater reliability is low (Schultz & Evans, 2012). A key implication of the current study is that adolescents should also be asked to complete the self-report versions of behavior rating scales, and unless parents or teachers report clinical levels of oppositional behaviors, the adolescent ratings should generally be considered as valid.…”
Section: Psychological Assessmentmentioning
confidence: 97%
“…Adolescent self-reports were more predictive of performance on an objective math task than parent ratings (Chan & Martinussen, 2016), whereas parent-reports were more strongly associated with educational attainment, high school GPA, and vocational performance than were self-reports of young adults with ADHD (Barkley et al, 2002). Although, compared to parent ratings, teacher ratings correlated more strongly with grades (GPA) and impairment (Sibley et al, 2014), inter-rater agreement between teachers on ADHD rating scales is low in secondary school (Evans et al, 2005), and those ratings are subject to rater biases such as teacher sex and age (Schultz & Evans, 2012).…”
mentioning
confidence: 99%
“…However, several studies have shown that this information can be influenced by the characteristics of the informant. For example, it has been shown that female young teachers tend to provide more severe scores than older male teachers (Schultz and Evans, 2012 ). In another study, Chi and Hinshaw predicted the discrepancies between the reports provided by the mother and the teacher based on the mother's responses to the Beck Depression Inventory (Chi and Hinshaw, 2002 ).…”
Section: Introductionmentioning
confidence: 99%